In Vitro Cytotoxic Study for Purified Resveratrol Extracted from Grape Skin Fruit Vitis vinifera - Zainab Y. Mohammed; Essam F. Al-Jumaily; Nahi Y. Yaseen (College of Pharmacy University of Baghdad, 2017)
This study  was  conducted  with the  aim to  extract and  purify  a  polyphenolic  compound  â€œ Resveratrolâ€ from the skin of black grapes Vitis vinifera cultivated in Iraq. The purified resveratrol is obtained after ethanolic extraction with 80% v/v solution for fresh grape skin, followed by acid hydrolysis   with   10%   HCl   solution then   the  aglycon   moiety   was  taken  with   organic   solvent ( chloroform). Using silica gel G60 packed glass column chromatography with mobile phase benzene: methanol: acetic acid  20:4:1 a partial purified resveratrol was obtained then preperative thin layer chromatography technique yielded pure crystals identified as resveratrol (mixture of two isomers cis and trans) in relation  to resveratrol standard (35 mg resveratrol crystals / 0.5 kg fresh grape skin was obtained as a result of these processes ). The study was also employed an in vitro evaluation the cytotoxic effect of pure resveratrol on some cell line including : the murine mammary adenocarcinoma AMN-3 cell line, the human laryngeal carcinoma (Hep-2) cell line and the Rat embryo fibroblast (Ref) cell line, at different concentrations and different expousure time. The cytotoxic effect of the pure resveratrol was studied in comparison with trans- resveratrol standard in concentrations of (12.5, 25, 50 and 100) Âµg/ml for both purified resveratrol and the standard, also the comparism included methotrexate drug in concentrations  (0.05 , 0.1 , 0.2 and 0.4)  Âµg/ml toward the growth effects of the three types of cell lines and at three exposure times (24, 48 and 72) hours. The cytotoxic inhibition effect for the purified extracted resveratrol revealed that the highest significant effect (P<0.01) was achieved after 24 hr of exposure on both AMN-3 and Ref cell lines. Hep-2 cell line responded to extracted resveratrol in different manners. Keywords: Resveratrol , grape skin , polyphenols, cytotoxic study